2012
DOI: 10.1371/journal.pone.0043401
|View full text |Cite
|
Sign up to set email alerts
|

Genome-Scale Reconstruction and Analysis of the Metabolic Network in the Hyperthermophilic Archaeon Sulfolobus Solfataricus

Abstract: We describe the reconstruction of a genome-scale metabolic model of the crenarchaeon Sulfolobus solfataricus, a hyperthermoacidophilic microorganism. It grows in terrestrial volcanic hot springs with growth occurring at pH 2–4 (optimum 3.5) and a temperature of 75–80°C (optimum 80°C). The genome of Sulfolobus solfataricus P2 contains 2,992,245 bp on a single circular chromosome and encodes 2,977 proteins and a number of RNAs. The network comprises 718 metabolic and 58 transport/exchange reactions and 705 uniqu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
56
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 50 publications
(56 citation statements)
references
References 73 publications
(101 reference statements)
0
56
0
Order By: Relevance
“…As revealed by the genome analysis of S. solfataricus P2, strain A20 lacks the classical Embden–Meyerhof–Parnas (EMP) and pentose phosphate pathways, since the genes encoding the homologs of the key enzymes in these pathways, i.e., phosphofructokinase in the former and glucose-6-phosphate dehydrogenase, 6-phosphogluconolactonase and 6-phosphogluconate dehydrogenase in the latter, are missing from the genomes (She et al, 2001; Ulas et al, 2012). Like other genome-sequenced Sulfolobus strains, strain A20 may utilize glucose through either the semi-phosphorylative or the non-phosphorylative-Entner-Doudoroff (ED) pathway, or both (Table 3).…”
Section: Resultsmentioning
confidence: 99%
“…As revealed by the genome analysis of S. solfataricus P2, strain A20 lacks the classical Embden–Meyerhof–Parnas (EMP) and pentose phosphate pathways, since the genes encoding the homologs of the key enzymes in these pathways, i.e., phosphofructokinase in the former and glucose-6-phosphate dehydrogenase, 6-phosphogluconolactonase and 6-phosphogluconate dehydrogenase in the latter, are missing from the genomes (She et al, 2001; Ulas et al, 2012). Like other genome-sequenced Sulfolobus strains, strain A20 may utilize glucose through either the semi-phosphorylative or the non-phosphorylative-Entner-Doudoroff (ED) pathway, or both (Table 3).…”
Section: Resultsmentioning
confidence: 99%
“…This exciting progress allowed the unraveling of protein function in vivo and qualifies Archaea as model organisms for synthetic biology and systems biology (303,397,398). Thus, within the last years, the first genome-wide metabolic models, flux balance analysis (FBA), as well as first detailed reaction kinetic models were established for Archaea (338,(399)(400)(401)(402)(403)(404). These studies also analyzed the responses to different carbon sources and, often performed in combination with biochemical studies, revealed new, exciting, deeper insights into the regulation of metabolic networks at the transcript and protein levels.…”
Section: Metabolic and Regulatory Characteristics Of Well-studied Arcmentioning
confidence: 99%
“…Later, Sul. solfataricus was established as a systems biology organism; a genome-scale model was established; and flux balance analysis (FBA) in response to different carbon sources was performed (303,399).…”
Section: Sulfolobus Solfataricusmentioning
confidence: 99%
“…This was followed in 2010 by a new GEM for a haloalkaliphile, Natronomonas pharaonis ( i OG654) [25], which inherited significantly from the H. salinarum model. The only other nonmethanogenic archaeal GEM to our knowledge was independently constructed in 2012 for the Sulfolobus solfataricus by Ulas et al [26]. …”
Section: Genealogy Of Archaeal Gemsmentioning
confidence: 99%